The skull of the Miocene Spheniscus urbinai (Aves, Sphenisciformes): osteology, brain morphology, and the cranial pneumatic systems - Acosta Hospitaleche, Carolina Ileana Alicia; Paulina Carabajal, Ariana; Yury Yáñez, Roberto (Journal of Anatomy)
Spheniscus urbinai represents one of four extinct Spheniscus species from the Cenozoic of southern South America, known from several poorly described diversely complete skulls and postcranial elements. Here, we present a review of the cranial osteology of all known specimens (collected in Argentina, Chile, and Peru), including a paleoneurological analysis using CT scans, and an exploration of its cranial pneumaticity compared to other extinct and living seabirds. Our results show that among Spheniscus species, S. urbinai exhibits slightly greater cranial pneumaticity than the living species. Additionally, we confirm previous findings which indicate that the marked reduction of cranial pneumaticity—which is characteristic of living penguins—occurred early during the Eocene (as observed in the Antarctic penguin MLP 12-I-20-1, but not in the coeval Anthropornis). Fil: Acosta Hospitaleche, Carolina Ileana Alicia. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. Departamento Científico de Paleontología de Vertebrados; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina Fil: Paulina Carabajal, Ariana. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Patagonia Norte. Instituto de Investigaciones en Biodiversidad y Medioambiente. Universidad Nacional del Comahue. Centro Regional Universidad Bariloche. Instituto de Investigaciones en Biodiversidad y Medioambiente; Argentina Fil: Yury Yáñez, Roberto. Universidad de Chile; Chile